DISIPLIN PEGAWAI DALAM PENGGUNAAN ATRIBUT KEPANGKATAN PADA SEKRETARIAT DAERAH PROVINSI BENGKULU - Junaidy, Chefran (Jurnal Governance dan Administrasi Publik, 2017)
This study is to determine the Employee Discipline In Using Attribute Ranks  In Bengkulu Provincial Secretariat in accordance with the Governor Regulation No.  14 of 2013 on uniforms and attributes of civil servants in the Department of  Government of Bengkulu Province. This is a qualitative research method. Sample interviews in this study were taken  from the 6 elements 2 and 4 structural officials staff. The sampling technique used in  this study sampling purposive research that took respondents by researchers  consideration. Data analysis was conducted through interviews with how repetitive  and continuous between data collection and analysis, either during data collection in  the field and after the data are collected. Data analysis was performed by 3 stages:  reduction, Display, and inference and verification. The results showed discipline in the use of Attribute Ranks Employee uniforms  Protection Society and Clothing Department Warana Legs In Bengkulu Provincial  Secretariat in accordance with the Governor Regulation No. 14 of 2013 on uniforms  and attributes of civil servants in the Department of Government of Bengkulu  province in the implementation has not been optimal. This is because there are many  staff or employees who do not comply with usage attribute uniforms, such as the  employee does not use the Board Names, Name / ID Card, Signs Rank, Name Tag,  WTP and Belt, Badges Korpri.